Extracorporeal membrane oxygenation in trauma: A single institution experience and review of the literature. Issue 12 (December 2018) - Strumwasser, Aaron; Tobin, Joshua M; Henry, Reynold; Guidry, Chrissy; Park, Caroline; Inaba, Kenji; Demetriades, Demetrios
Introduction: Limited options exist for cardiovascular support of the trauma patient in extremis. This patient population offers challenges that are often considered insurmountable. This article identifies a heterogeneous group of trauma patients in extremis who may benefit from extracorporeal membrane oxygenation. Methods: Data were sourced from the medical records of all patients placed on extracorporeal membrane oxygenation following trauma at a Level I Trauma Center between 1 December 2016 and 1 December 2017. Results: All patients were male (N = 7), mostly with blunt injuries (n = 5), with an average age of 41 years and with an average Injury Severity Scores of 33 (median = 34). Two out of seven patients survived (28.5%). Survivors tended to have a longer duration on extracorporeal membrane oxygenation (13.5 vs 3.8 days), had extracorporeal membrane oxygenation initiated later (15 vs 7.8 days), and had suffered a blunt injury. Two patients were initiated on veno-arterial extracorporeal membrane oxygenation (both non-survivors) and five were initiated on veno-venous extracorporeal membrane oxygenation (two survivors, three non-survivors). Five patients were heparinized immediately (one survivor, four non-survivors), and two patients were heparinized after clotting was noted in the circuit (one survivor, one non-survivor). Three of the seven (42.8%) patients suffered cardiac arrest either prior to, or during, the initiation of extracorporeal membrane oxygenation (all non-survivors). Discussion: Extracorporeal membrane oxygenation use in the trauma patient in extremis is not standard; however, this article demonstrates that extracorporeal membrane oxygenation is feasible in a complex, heterogeneous patient population when treated at designated centers.